Про задачу ідентифікації динаміки дискретно керованого розподіленого просторово-часового процесу - Скопецький, В.В.; Стоян, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
An identification-pseudoinverse approach to the construction of integral models of the distributed space-time systems with regard for discretely observed external dynamical disturbances and the system's state corresponding to them is proposed. The problem of the control over such systems is solved. The results obtained are illustrated.